Exploring the Mediating Role of Green Transformational Leadership in the Relationship between Corporate Social Responsibility and Environmental Performance - Barati, Mohammad; Masoumi, Seyed Rasool; Ramezanzadeh Zeidi, Abbas (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2026)
Objective: The present study aimed to investigate the mediating role of green transformational leadership in the relationship between corporate social responsibility (CSR) and environmental performance among companies listed on the Tehran Stock Exchange.Methods and Materials: This applied research employed a descriptive–correlational survey design. The statistical population consisted of financial managers, heads of accounting departments, and senior accounting experts working in companies listed on the Tehran Stock Exchange in 2025. Using Cochran’s formula and a stratified random sampling approach, 395 valid questionnaires were collected and analyzed. Standardized instruments were used to measure corporate social responsibility, green transformational leadership, and environmental performance. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS 3 software. Reliability, convergent validity, discriminant validity, and overall model fit were assessed prior to hypothesis testing. The results confirmed satisfactory psychometric properties and a strong model fit (GOF = 0.672), indicating the adequacy of the measurement and structural models.Findings: The structural model results demonstrated that corporate social responsibility had a significant positive effect on environmental performance (β = 0.414, t = 9.370, p < 0.001). Corporate social responsibility also exerted a significant positive effect on green transformational leadership (β = 0.739, t = 29.310, p < 0.001). Furthermore, green transformational leadership significantly enhanced environmental performance (β = 0.584, t = 13.958, p < 0.001). The findings additionally confirmed the mediating role of green transformational leadership in the relationship between corporate social responsibility and environmental performance, indicating that CSR contributes to superior environmental outcomes both directly and indirectly through the development of green transformational leadership practices.Conclusion: The findings indicate that corporate social responsibility serves as a strategic driver of environmental performance and that green transformational leadership plays a pivotal intermediary role in translating social commitments into tangible environmental achievements.